THE INFLUENCE OF SERVICE QUALITY, SERVICE RESPONSIVENESS, AND CUSTOMER SERVICE COMPETENCE ON CUSTOMER SATISFACTION AMONG USERS OF THE HALO BCA CONTACT CENTER SERVICE - Sonia Sonia; Agung Priyono; Fahri Haikal; Akhmad Hairul Umam; Vitrio Wibisono (Journal of Management and Leadership, 2026)
The intense competition in the banking industry today requires financial institutions to continuously adapt to the increasingly dynamic needs of society. Service quality has become a crucial factor for banks in maintaining customer trust and loyalty. As the frontline of customer interaction, effective communication between the bank and its customers through customer service plays a key role in preserving the institution's reputation. This study aims to examine the effect of service quality, service responsiveness, and customer service competence on customer satisfaction in the Halo BCA contact center service. Service quality refers to the overall evaluation of customers regarding the excellence of a service. Service responsiveness, is one of the main dimensions used to assess how promptly a company handles customer complaints. Competence refers to the combination of technical knowledge and interpersonal skills possessed by service officers. The population in this study consists of customers of Bank Central Asia (BCA), with a sample of 100 respondents. The sampling technique used is Purposive Sampling. Data were collected by distributing questionnaires to BCA customers via the WhatsApp application, and the data were analysed using the SmartPLS 4.0 program. The results of the study indicate that service quality has no significant effect on customer satisfaction. Service responsiveness does not have a significant effect on customer satisfaction. Meanwhile, Customer service competence has a positive and significant effect on customer satisfaction.